Livello di dipendenza dai Servizi Territoriali e costi relativi al trattamento della schizofrenia - D’Allio, Giorgio; Rutto, Fernando; Coppi, Michela; Guidi, Luca (Farmeconomia. Health Economics and Therapeutic Pathways, 2005)
The present study was designed to evaluate the level of dependence from Mental Health Care Department, in Casale Monferrato, of three groups of psychotic patients treated with olanzapine (31), risperidone (30) or typical neuroleptics (31). The observation was retrospective, lasting one year (2003-2004), and collected data relative to health care resources as specialist visits, home interventions operated by nurses or physicians, drug administration, rehabilitation, psychotherapy, hospitalizations. The data collected allowed to evidentiate substantial differences among olanzapine and risperidone treated patients, usually younger, versus typical treated patients, usually older and more chronic. In general, atypical treated patients, evidentiate a reduction of home nurse intervention in respect to typical treated patients while olanzapine shows a trend in hospitalization and specialist visits reduction versus risperidone. Total health care costs are not significantly different among the three groups but evidentiate interventions more oriented to rehabilitation in the group treated with olanzapine while risperidone treated patients needed a major number of hospitalizations. Typical treated patients requested, instead, an high number of home intervention due to their chronic conditions and cognitive imparement.